Normal Kidney Size in Nepalese Female at KMCTH - Badu, Muna; Rajbhandari, Shankar Bahadur Singh; Regmi, Pashupati (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Baseline knowledge of normal kidney size is essential when evaluating patients with possible renal disease. This study was done to assess normal kidney size in Nepalese female at Kathmandu Medical College Teaching Hospital. MATERIALAND METHODS: Prospective hospital based cross sectional study was conducted including 231 adult females without any known renal diseases from November 2018 to February 2019. Renal length was measured as longest pole to pole distance. Renal width was measured as the maximum dimension in the cross section at the level of the renal hilum. Cortical thickness was measured between outer renal margin and renal sinus in transverse plane. RESULTS: The mean length of right and left kidneys were 96.53±8.29 mm and 100.47±9.15 mm respectively with a range of 76-120 mm and 78-120 mm respectively. The mean renal width was 46.80±6.87 mm for right kidneys and 48.61±6.64 mm for left kidneys. The mean cortical thickness were 17.03±3.58 mm for right kidneys and 17.43±3.73 mm for left kidneys. There was significant correlation between length of right and left kidney, however there was no significant correlation between kidney length with kidney width and kidney length with cortical thickness. There was no significant correlation of renal parameters with age, height, weight and body mass index. CONCLUSION: Normal kidney size of Nepalese females visiting Kathmandu Medical College was comparable to the previous studies. This will help as future reference to evaluate abnormal kidney sizes.